Sauromatum guttatum extract promotes wound healing and tissue regeneration in a burn mouse model via up-regulation of growth factors. (1st January 2019) - Said, Ali; Wahid, Fazli; Bashir, Kashif; Rasheed, Hafiz Majid; Khan, Taous; Hussain, Zohaib; Siraj, Sami
Abstract: Contexts: Sauromatum guttatum (Wall.) Schott (Araceae) has been traditionally used for the treatment of wounds. Objectives: This study evaluates the healing and tissue regeneration potential of S. guttatum extract in burn wounds. Materials and methods: S. guttatum extract was analysed using various chemical tests, thin layer chromatography (TLC) and high-performance liquid chromatography (HPLC). Moreover, the extract was tested against burn associated bacteria and minimum inhibitory concentration (MIC) was also calculated. Wound healing and tissue regeneration potential was assessed using a thermally induced burn BALBc mouse model. S. guttatum extract (2% w / w ) prepared in petroleum jelly, vehicle and positive control [silver sulfadiazine (SD)] groups was applied three times a day. The treatment was continued for 15 d and wound closure was measured and photographed on day 5, 10 and 15. The burnt tissues excised from wounds were subjected to histological and comparative gene expression analysis. Results: The results of the chemical tests indicated the presence of alkaloids, saponins, phenols, phytosterols, tannins, and flavonoids, while TLC and HPLC analysis indicated the presence of various compounds. The extract showed excellent activity against the tested pathogens. The lowest MIC (125 µg/mL) was observed against Staphylococcus aureus . A considerable decrease in wound area (72%) was observed in extract-treated group. Histological examination of extract-treated group showed good signs of wound healing with complete re-epithelialization and better tissue regeneration. Comparative gene expression analysis revealed the up-regulation of wound healing related PDGF, EGF and FGF genes. Conclusions: S. guttatum extract may be used to isolate bioactive constituents for the treatment of burn wounds.